Employment and wage premiums in South African manufacturing exporters: Firm-level evidence. Issue 5 (3rd September 2019) - Bezuidenhout, Carli; Matthee, Marianne; Rankin, Neil
ABSTRACT: South Africa is currently suffering from high unemployment. As export activity is generally associated with higher economic growth, productivity, employment levels and wages, this papers investigates if increasing export activity is one of the solutions to the high unemployment levels in South Africa. By using newly made available administrative data on the population of South African firms, this paper aims to deepen the understanding of the wage premium, employment premium and employment growth of exporters relative to non-exporters (as well as within exporters). By following the methodology of Bernard and Jensen, the results show that South African manufacturing exporters do have an employment premium and wage premium. But advocating increased export activity is not enough, as exporting firms are heterogenous. Furthermore, employment growth of exporters (measured by estimating first-difference regressions) is faster than non-exporters, but growth in jobs is skewed towards higher skilled, more experience workers.